Emansipasi Intelektual Jacques Rancière: Kritik Radikal atas Paradoks Kesetaraan dalam Pendidikan Kritis - Drianus, Oktarizal; Meitikasari, Diah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
This paper aims to show at once critics and solutions for the logic of critical education, which has recently been sporadically appropriated by educational institutions and communities in Indonesia. This paper uses the method of library research with primary sources, namely: The Ignorant Schoolmaster: Five Lessons in Intellectual Emancipation by Jacques Rancière. Findings shed light on several things, namely: 1) Rancière's critics of critical education which perpetuates the paradox of equality; 2) The experience of “the teacher who did not know”, Josep Jacotot who accidentally found a way of learning that emancipated his students; 3) Rancière’s criticism of the explicative order which perpetuated the myth of pedagogy. Therefore, the world is divided into two: superior intelligence and inferior intelligence. So that, it made up the imaginary distance, thus it tied the domination relation between the master of explicator and the subordinated ones; 4) Rancière’s critics of the fundamental assumptions of critical education that it puts equality as teleological fiction. In fact, it plunges us into a spiral of stultification. Rancière opposed it. Thus, the presupposition of equality must be put in place as an emancipatory point of departure; 5) the notion of natural universal teaching as a way of learning for everyone. Tulisan ini bertujuan untuk menunjukkan kritik sekaligus solusi atas logika pendidikan kritis yang akhir-akhir ini diapropriasi secara sporadis oleh lembaga pendidikan maupun komunitas-komunitas di Indonesia. Tulisan ini menggunakan metode kajian kepustakaan dengan sumber primer, yaitu: The Ignorant Schoolmaster: Five Lessons in Intellectual Emancipation karya Jacques Rancière. Temuan dari kajian ini memuat beberapa hal, yaitu: 1) Kritik Rancière terhadap pendidikan kritis yang menyimpan paradoks kesetaraan; 2) pengalaman sang guru yang tidak tahu, Josep Jacotot; 3) Kritiknya terhadap rezim penjelasan yang turut melanggengkan mitos pedagogis. Karenanya, dunia terbagi menjadi dua: kecerdasan superior dan kecerdasan inferior sehingga menciptakan jarak imajiner dan ketergantuan yang terus dikonfirmasi oleh pihak dominan terhadap pihak subordinat; 4) kritik terhadap asumsi pendidikan kritis yang meletakkan kesetaraan sebagai fiksi teleologis yang justru menjerumuskan kita ke dalam spiral pembodohan. Rancière menepisnya bahwa semestinya pra-andaian kesetaraan mesti diletakkan sebagai titik berangkat pendidikan yang emansipatoris; 5) Tawaran Pengajaran Universal-Alamiah sebagai cara belajar untuk semua orang.